2021
DOI: 10.1017/s0007114521001513
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplementing a healthy diet with pecan nuts or extra-virgin olive oil on inflammatory profile of patients with stable coronary artery disease: a randomised clinical trial

Abstract: The consumption of nuts and extra-virgin olive oil has been associated with suppression of inflammatory pathways that contribute to atherosclerosis, but its role on the modulation of the inflammatory profile in patients with established coronary artery disease (CAD) is unclear. The aim of this study was to evaluate the effects of adding pecan nuts or extra-virgin olive oil to a healthy diet on inflammatory markers in patients with stable CAD. In this randomized clinical trial, 204 patients were enrolled to thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Studies have established a correlation between the consumption of nuts and extra-virgin olive oil and the inhibition of multiple mechanisms, including inflammatory pathways that are responsible for atherosclerosis 21,22 . However, this strategy has not successfully reduced inflammatory markers in patients with CCD 23 . Interestingly, in a randomized controlled trial (RCT) among CCD patients, the addition of nuts to a healthy diet decreased non-high-density lipoprotein cholesterol (HDL-C) levels, but no effects on low-density lipoprotein cholesterol (LDL-C) were reported 24 .…”
Section: Physical Activity and Dietmentioning
confidence: 97%
“…Studies have established a correlation between the consumption of nuts and extra-virgin olive oil and the inhibition of multiple mechanisms, including inflammatory pathways that are responsible for atherosclerosis 21,22 . However, this strategy has not successfully reduced inflammatory markers in patients with CCD 23 . Interestingly, in a randomized controlled trial (RCT) among CCD patients, the addition of nuts to a healthy diet decreased non-high-density lipoprotein cholesterol (HDL-C) levels, but no effects on low-density lipoprotein cholesterol (LDL-C) were reported 24 .…”
Section: Physical Activity and Dietmentioning
confidence: 97%
“…The convenience sample was a quick and convenient method and all 37 participants willing to participate met the inclusion criteria: population of healthy volunteers, aged between 18 and 55 years old, with a body mass index between >18.0 kg/m 2 and (BMI) ≤ 30 m/kg 2 and who normally included olive oil in their diet. The study aimed to assess the impact of a ±30 mL daily intake of an NPPR-EVOO for a period of 100 consecutive days, which is also used in similar clinical studies [26].…”
Section: Study Design and Recruitmentmentioning
confidence: 99%
“…A 2022 randomized case‐control trial involving 102 individuals with HIV receiving anti‐retroviral therapy (aRVT) showed the benefits of the MD on the microbiome in the setting of HIV. One group followed an MD supplemented with 50 g/day of EVOO and 30 g/day of walnuts (which have been linked to decreased inflammation 5 ) and the other group followed an unmodified diet for 12 weeks. They found that the participants in the MD group with a high MD adherence score (7–10) showed an increased prevalence of Burkholderiales , Butyrivibrio , Catenibacterium , and Succinovibrio bacterial colonies.…”
Section: Microbiome Enhancing Dietary Considerationsmentioning
confidence: 99%